Incorporação do permanganato de potássio à cera de carnaúba visando a conservação de mamão papaia (Carica papaya) - Albuquerque, Fernanda Déo [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Papaya is considered a fruit of great economic importance for Brazil. However, as it is a climacteric fruit, it has a reduced post-harvest shelf life, which impacts its commercialization. The use of modified atmosphere (MAP), such as the application of carnauba wax, is a technology used to minimize the fresh weight loss and improve the qualitative aspects of this fruit. Likewise, potassium permanganate (KMnO4) is also used to reduce the ethylene concentration and, consequently, extend post-harvest shelf life. However, no reports were found regarding the use of microencapsulated KMnO4 incorporated into carnauba wax. Thus, the objective of this study was to verify the effect of the incorporation of microencapsulated KMnO4 into carnauba wax aiming the conservation of papaya. Papaya fruit of Solo group at maturity stage M3, fruit with 50 – 75% of the yellow surface with light green areas, were submitted to the following treatments: negative control (C-), fruit without immersion in carnauba wax and KMnO4; positive control (C+), fruit immersed only in carnauba wax; fruit immersed in carnauba wax containing 2% (w/v) of KMnO4 (C+2%); fruit immersed in carnauba wax containing 4% (w/v) of KMnO4 (C+4%). The fruit were stored at room temperature (~ 22°C and 55% RH) for 9 days. The fruit were evaluated for fresh weight loss, skin and pulp color and physicochemical parameters. The incorporation of microencapsulated KMnO4 into carnauba wax at different concentrations did not result in significant differences in relation to the control treatments. On the other hand, changes were observed in the parameters of skin and pulp color during storage and reduction of fruit firmness. Thus, the incorporation of microencapsulated KMnO4 into carnauba wax did not result in better post-harvest conservation of papaya fruits.

O mamão é considerado um fruto de grande importância econômica para o Brasil. Todavia, por ser um fruto climatério, esse apresenta uma vida útil póscolheita reduzida, o que impacta na sua comercialização. O uso de atmosfera modificada (MAP), como a aplicação da cera de carnaúba, é uma tecnologia utilizada para minimizar a perda de massa fresca e melhorar os aspectos qualitativos deste fruto. Da mesma forma, o permanganato de potássio (KMnO4) também é utilizado visando diminuir a concentração de etileno e, consequentemente, aumentar a vida útil pós-colheita. Todavia, não foram encontrados relatos quanto ao uso de KMnO4 microencapsulado incorporado à cera de carnaúba. Desta forma, o objetivo desse trabalho foi verificar o efeito da incorporação de KMnO4 microencapsulado à cera de carnaúba visando a conservação de mamão papaia. Frutos de mamoeiros do grupo Solo no estádio de maturação M3, frutos com 50 – 75% da superfície amarela com áreas próximas em verde-claro, foram submetidos aos seguintes tratamentos: controle negativo (C-), frutos sem imersão em cera de carnaúba e KMnO4; controle positivo (C+), frutos imersos apenas em cera de carnaúba; frutos imersos em cera de carnaúba contendo 2% (m/v) de KMnO4 (C+2%); frutos imersos em cera de carnaúba contendo 4% (m/v) de KMnO4 (C+4%). Os frutos foram acomodados a temperatura ambiente (~ 22°C e 55% UR) por 9 dias. Os frutos foram avaliados conforme à perda de massa fresca, coloração da casca e polpa e parâmetros físico-químicos. A incorporação de KMnO4 microencapsulado à cera de carnaúba nas diferentes concentrações não resultou em diferenças significativas em relação aos tratamentos controle. Por outro lado, foram observadas mudanças nos padrões da coloração da casca e polpa durante o armazenamento e redução da firmeza dos frutos. Desta forma, a incorporação de KMnO4 microencapsulado à cera de carnaúba não resultou em melhor conservação pós-colheita dos frutos de mamoeiros.
Incorporation of potassium permanganate in carnauba wax for the preservation of papaya (Carica papaya)
Keywords: Mamão; Microencapsulação; Cera de carnaúba; Revestimentos